Lagged Wetland CH4 Flux Response in a Historically Wet Year. Issue 11 (1st November 2021) - Turner, J.; Desai, A. R.; Thom, J.; Wickland, K. P.
Abstract: While a stimulating effect of plant primary productivity on soil carbon dioxide (CO2 ) emissions has been well documented, links between gross primary productivity (GPP) and wetland methane (CH4 ) emissions are less well investigated. Determination of the influence of primary productivity on wetland CH4 emissions (FCH4 ) is complicated by confounding influences of water table level and temperature on CH4 production, which also vary seasonally. Here, we evaluate the link between preceding GPP and subsequent FCH4 at two fens in Wisconsin using eddy covariance flux towers, Lost Creek (US‐Los) and Allequash Creek (US‐ALQ). Both wetlands are mosaics of forested and shrub wetlands, with US‐Los being larger in scale and having a more open canopy. Co‐located sites with multi‐year observations of flux, hydrology, and meteorology provide an opportunity to measure and compare lag effects on FCH4 without interference due to differing climate. Daily average FCH4 from US‐Los reached a maximum of 47.7 ηmol CH4 m −2  s −1 during the study period, while US‐ALQ was more than double at 117.9 ηmol CH4  m −2  s −1 . The lagged influence of GPP on temperature‐normalized FCH4 ( T air ‐FCH4 ) was weaker and more delayed in a year with anomalously high precipitation than a following drier year at both sites. FCH4 at US‐ALQ was lower coincident with higher stream discharge in the wet year (2019), potentially due to soil gas flushing during high precipitation events and lower water temperatures. Better understanding of the lagged influence of GPP on FCH4 due to this study has implications for climate modeling and more accurate carbon budgeting. Plain Language Summary: Research on what controls wetland methane emissions is continually advancing, and while this is beneficial for predicting future climate scenarios, there is still a need to understand how changes in plant productivity will influence wetland methane emissions. In this study, we investigated the strength and lag time of the relationship between gross primary productivity due to photosynthesizing plants and wetland methane flux in two closely situated sites. We also looked at how hydrology might change that relationship. We found the total amount of methane emitted in an extremely wet year was less than what was emitted in the following drier year at both wetlands potentially because of less carbon provided to the soil by photosynthesizing plants. The difference in methane emissions from one year to the next could be influenced by wetland hydrology, water temperature, or other conditions that impact methane‐producing bacteria. Results from this study will help scientists better predict methane emissions following high precipitation years which may become more common in a changing climate. Key Points: Analyzed lagged response of methane flux to different driver variables at two closely located fen wetlands in Wisconsin Air‐temperature normalization of methane flux was crucial for interpretation of lagged responses, especially in wet year Lagged response of methane flux to gross primary productivity surpassed 60 days and had weaker correlation during wet year at both sites